Bothrops pauloensis Snake Venom Toxins: The Search for New Therapeutic Models - M. Rodrigues, Veridiana; S. Lopes, Daiana; E. Castanheira, Leticia; N. C. Gimenes, Sarah; L. Naves de Souza, Dayane; C. Ache, David; P. Borges, Isabela; A.G. Yoneyama, Kelly; Renata (Current Topics in Medicinal Chemistry, 2015)
Snake venoms constitute a mixture of bioactive components that are involved not only in envenomation pathophysiology but also in the development of new drugs to treat many diseases. Different enzymatic and non-enzymatic proteins, such as phospholipases A2, hyaluronidases, L-amino acid oxidases, metalloproteinases, serine proteinases, lectins and disintegrins have been isolated and their functional and structural properties described in the literature. Many of these studies have also explored their medicinal potential focusing mainly on anticancer, antithrombotic and microbicide therapies. Bothrops pauloensis is a species found in Brazil, whose venom has been the focus of our studies in order to explore the biochemical and functional characteristics of their components. In this review, we have presented the main results of years of research on different toxins from B. pauloensis emphasizing their therapeutic potential. Studies concerning snake venom toxins to search for new therapeutic models open perspectives for new drug discovery.
Keywords: Antithrombotic